When Knowledge is Power: Three Models of Change in International Organizations - Haas Ernst B. (Berkeley: University of California Press, 1990)
"When Knowledge is Power" is a wide-ranging work that will elicit interest from political scientists, organization theorists, bureaucrats, and students of management and international administration.
Inv.: (NP(B/11197s
Keywords: international -- organizations -- communication -- learning